Penerapan E-Government Dalam Pelayanan KTP Pada Dinas Kependudukan dan Pencatatan Sipil Kota Padang - Shellya Salsabila; Aidinil Zetra; Roni Ekha Putera (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2021)
In life, the role of service is very large, including public service. Every service agency is obliged to improve the quality of service. The poor quality of public services in Indonesia must be immediately addressed by the government. One of the government's efforts to improve the quality of public services is by utilizing advances in information technology in the process of governance. This is known as e-government or the administration of electronic or internet-based government. The process of implementing e-government through several stages, web presence, interaction, transaction and transformation. One way to improve services is to follow the development of more effective information technology. So that it can encourage the government to accelerate e-government, which is an effort to improve electronic-based government services. With the e-government system, it is hoped that every public service agency can provide an increase in the quality of public services that are more transparent, effective and efficient. For online services, the people of Padang City can already access it, but there are still a number of obstacles in its operation. This study aims to determine the application of e-government in making ID cards at the Population and Civil Registration Office of Padang City. This study uses the theory of Nugroho (2007), the stages of development of the implementation of e-government in Indonesia are divided into four and to see the indicators of effectiveness using the theory of Sondang P Siagian. Data collection techniques are interviews, documentation and observation. The research method used is qualitative with descriptive type. The informant selection technique was purposive sampling and tested the validity of the researcher's data by triangulation of sources. The results of the study indicate that public services at the Padang City Population and Civil Registration Service in using the website are still not effective. There are still obstacles in its implementation, which are related to servers and networks that sometimes have problems, besides that socialization needs to be improved so that public and bureaucrats awareness increases in utilizing e-government development in Padang City